Allometric trajectories of body and head morphology in three sympatric Arctic charr (Salvelinus alpinus (L.)) morphs. Issue 18 (8th August 2017) - Simonsen, Marianne Knutsdotter; Siwertsson, Anna; Adams, Colin Ean; Amundsen, Per‐Arne; Præbel, Kim; Knudsen, Rune
Abstract: A study of body and head development in three sympatric reproductively isolated Arctic charr ( Salvelinus alpinus (L.)) morphs from a subarctic lake (Skogsfjordvatn, northern Norway) revealed allometric trajectories that resulted in morphological differences. The three morphs were ecologically assigned to a littoral omnivore, a profundal benthivore and a profundal piscivore, and this was confirmed by genetic analyses (microsatellites). Principal component analysis was used to identify the variables responsible for most of the morphological variation of the body and head shape. The littoral omnivore and the profundal piscivore morph had convergent allometric trajectories for the most important head shape variables, developing bigger mouths and relatively smaller eyes with increasing head size. The two profundal morphs shared common trajectories for the variables explaining most of the body and head shape variation, namely head size relative to body size, placement of the dorsal and pelvic fins, eye size and mouth size. In contrast, the littoral omnivore and the profundal benthivore morphs were not on common allometric trajectories for any of the examined variables. The findings suggest that different selective pressures could have been working on traits related to their trophic niche such as habitat and diet utilization of the three morphs, with the two profundal morphs experiencing almost identical environmental conditions. Abstract : This morphological study demonstrates distinct differences in the allometric trajectories between three genetically differentiated Arctic charr morphs in Lake Skogsfjordvatn, northern Norway. We observed allometric scaling (i.e., a change in morphology with size) in several of the studied PC axes, and the three morphs showed clear evidence of differences in allometry, reflecting different growth trajectories.